Histoplasma capsulatum modulates the immune response exerted by mesenchymal stromal cells (2022)
ABSTRACT: Mesenchymal stromal cells (MSCs) have become a tool not only for tissue regeneration but also for the treatment of inflammatory diseases. Several studies have demonstrated the therapeutic potential of MSCs for the treatment of noninfectious inflammatory diseases; however, they appear to play a dual role in infectious diseases. Histoplasmosis is a systemic mycosis caused by Histoplasma spp., which occurs mainly in immunosuppressed individuals; this mycosis can present a severe clinical picture with dissemination to various organs, and is associated with an exacerbated inflammatory response and with anemia and pancytopenia if bone marrow is affected. So far, the effect of a possible interaction of Histoplasma with stem cells present in the bone marrow is unknown.